2022
DOI: 10.1159/000527906
|View full text |Cite
|
Sign up to set email alerts
|

Effects up to 20-Year Follow-Up of Preventive Cognitive Therapy in Adults Remitted from Recurrent Depression: The DELTA Study

Abstract: <b><i>Introduction:</i></b> Major depressive disorder (MDD) is common, and recurrence rates are high. Preventive Cognitive Therapy (PCT), has been shown to prolong time to recurrence and reduce risk of recurrence(s) over 2–10 years in patients with recurrent depression. <b><i>Objective:</i></b> The aim of the study was to examine the effectiveness of PCT over 20 years on time to first recurrence, cumulative proportion of first recurrences, percentage of depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Although chronic cases account for over four fifths of the disease burden, these cases are not adequately addressed by the current healthcare system. Given the lifelong course of the disease in many cases, a long-term perspective and more flexible strategies to manage depression are needed (Bockting et al , 2015 ; Legemaat et al , 2023 ). During symptom-free periods, low-intensity digital interventions might be applied to prolong periods of well-being and monitor symptoms in order to detect relapses and initiate adequate treatment without delays (Kordy et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although chronic cases account for over four fifths of the disease burden, these cases are not adequately addressed by the current healthcare system. Given the lifelong course of the disease in many cases, a long-term perspective and more flexible strategies to manage depression are needed (Bockting et al , 2015 ; Legemaat et al , 2023 ). During symptom-free periods, low-intensity digital interventions might be applied to prolong periods of well-being and monitor symptoms in order to detect relapses and initiate adequate treatment without delays (Kordy et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The positive fantasizing technique is part of the PCT intervention [ 22 ]. PCT has been shown to be effective in preventing for depressive relapse and reducing depressive symptoms [ 13 , 15 , 16 , 18 , 19 , 42 ]. In our previous study [ 29 ], we isolated a short fantasizing exercise of ten minutes from the full protocol, and found that a single session was effective at reducing negative affect when measured directly after the single-session intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Two psychological interventions, namely positive fantasizing and mindfulness , are core therapeutic components of multiple sessions protocolized treatments. Preventive Cognitive Therapy (PCT) delivered during the remitted phase has proven effective in lowering relapse risk [ 13 19 ]. Positive fantasizing is a core component of PCT that is aimed at challenging dysfunctional attitudes and schemas by using positive phantasy with help of imagery, enhancing positive affect and positive cognitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population studies suggest that mental health may be improved through lifestyle elements such as physical exercise, 44 social activity, 45 and diet composition. 46,47 However, for any individual it may be challenging to reveal which lifestyle changes or therapies 48 work. Data on traditional end points such as recurrence may take long to obtain.…”
Section: How To Construct Mechanistic Modelsmentioning
confidence: 99%